Adopsi dan Difusi Teknologi Pengukuran Tekanan Intraokular Non-Invasif Pada Pemeriksaan Kesehatan di Kota Semarang - Sari Ayu Wulandari; Wisnu Adi Prasetyanto; Cynthia Arsita; Arga Dwi Pambudi (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2026)
The Community Service Program (PKM) in Semarang City, Central Java, aims to address the low adoption of smart city technology, particularly in health screening initiatives. Amid a rising prevalence of glaucoma, the rate of eye disease screening in this region remains low. This PKM initiative offers the development of an affordable, non-invasive tonometer for intraocular pressure measurement to facilitate early glaucoma screening and monitoring. The implementation includes device design, screening participation surveys, and analysis of measurement results compared to a reference tonometer. This tool is expected to aid in early glaucoma detection and help reduce adoption barriers to technology. Surveys conducted before and after the program indicate increased public understanding, while calibration tests show the device has high accuracy with a minimal error rate of 1.71 mmHg, demonstrating its effectiveness for intraocular pressure screening.